2021
DOI: 10.1016/j.immuni.2021.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Conventional type I dendritic cells maintain a reservoir of proliferative tumor-antigen specific TCF-1+ CD8+ T cells in tumor-draining lymph nodes

Abstract: Highlights d Longitudinal scRNA-seq of tumor-specific TCF-1 + CD8 + T cells in KP lung adenocarcinoma d Identified a proliferative Slamf6 + TCF-1 + T cell subset and a non-cycling SlamF6 À subset d The lymph node contains a recruitable reservoir of functional TCF-1 + CD8 + T cells d Flt3L+CD40 boosts cDC1, increases TCF-1 + CD8 + T cell frequencies, decreases tumor burden

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(120 citation statements)
references
References 60 publications
7
113
0
Order By: Relevance
“…One possible explanation for our results would be enhanced migration of antigen-loaded CD103 + cDC1s into the draining lymph nodes, potentially resulting in expansion of the antigen-specific TCF1 + stem-like population of CD8 + T cells that are necessary to maintain an immune response within tumors. 14 15 This could also be CXCR3 dependent, as CXCL9 expression by myeloid cells within the lymph nodes is important for memory responses to viral infections. 16 To evaluate this, we made use of a PyMT tumor cell line expressing the pH-insensitive fluorophore ZsGreen (PyMT-ZsGreen).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for our results would be enhanced migration of antigen-loaded CD103 + cDC1s into the draining lymph nodes, potentially resulting in expansion of the antigen-specific TCF1 + stem-like population of CD8 + T cells that are necessary to maintain an immune response within tumors. 14 15 This could also be CXCR3 dependent, as CXCL9 expression by myeloid cells within the lymph nodes is important for memory responses to viral infections. 16 To evaluate this, we made use of a PyMT tumor cell line expressing the pH-insensitive fluorophore ZsGreen (PyMT-ZsGreen).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of the TDLN in mediating a robust, RT-stimulated, anti-tumor response and RT s synergy with ICI has recently been reported, but only begun to be characterized [67,68]. The TDLN plays a critical role in T cell stimulation through activating DCs and concentrating tumor antigens [67,69,70]. Furthermore, there appears to be a progenitor sub-population of CD8 + T cells both within the tumor and TDLN that is critical for robust PD-1 therapy responses [71,72].…”
Section: Pre-clinical Datamentioning
confidence: 99%
“…Nevertheless, our data suggests that cDC-1s may have an inherent capacity to promote memory fate, which may contribute to the T MEM niche. In support of this proposed function, recent evidence demonstrated that cDC-1s are critical for maintaining a reservoir of stem-like cells in tumor-draining lymph nodes (Schenkel et al 2021). It is interesting to note that cDC-1s can bias CD4+ T cells towards the T REG lineage, which can be potent sources of TGF-b, whereas cDC-2s tend to induce an effector T helper 1 (T H1 ) fate (Brown et al, 2019;Opejin et al, 2020).…”
Section: Discussionmentioning
confidence: 92%